PEMANFAATAN MEDIA SOSIAL INSTAGRAM OLEH LEMBAGA ACT DALAM MENARIK MINAT PARA MASYARAKAT KOMUNITAS MUSLIM MEDAN - Debby Caroline Caroline (Fakultas Agama Islam Universitas Tjut Nyak Dhien, 2023)
ABSTRACT This study intends to seek knowledge about the process of using the social media of Aksi Cepat Tanggap (ACT) at the Medan branch office in increasing the awareness of the Muslim community in the city of Medan. This research also intends to find out how the communication effectiveness of the Aksi Cepat Tanggap (ACT) Medan branch office is in building a sense of concern for the Muslim community in the city of Medan so that they can help each other in need of assistance. Through social media owned by ACT's Medan branch, we can find out what obstacles are experienced in increasing the awareness of the Muslim community. The research approach used is a qualitative descriptive approach, because the research explains the phenomena that occur by collecting data obtained from research informants. The data collection technique used is to conduct direct interviews with informants by means of question and answer. Then do the documentation. Documentation was obtained through the ACT website, Instagram, and Facebook used by ACT. The results show that the process of using social media starts from the process of making a narrative by the Marketing Communication team and volunteers, then the process of sharing photos and videos that match the narrative that has been made, and continues with the process of posting to social media. Research shows that the communication effectiveness of the ACT branch of the Medan branch through social media is said to be effective, because it can be seen from the many interest responses that go directly through social media, which is then proven by donations that come in almost every day to the ACT institution. Based on the information that people get from social media, they are interested in donating in various types, ranging from money, gold, food, clothing, and transportation. Keywords: ACT Medan, Effectiveness, Social Media